COMMUNITY EMPOWERMENT THROUGH ORGANIC WASTE PROCESSING INTO AN APPROPRIATE PRODUCT TO ACTUALIZE KALIPURO VILLAGE IN BANYUWANGI AS INDEPENDENT VILLAGE - Ferdiana; Idiawati, Riris; Rosyidah, Aminatur (Proceedings of Annual Conference on Community Engagement, 2023)
Indonesia is a developing country and also one of the largest waste contributors in the world. Based on data from the Ministry of Environment and Forestry (KLHK), Indonesia produced 67.8 million tons of waste in 2020. Every village has the potential and opportunity to develop and prosper and improve the family economy by utilizing the potential resources that exist around their environment, which were originally considered as worthless goods to be of sale value, one of which is waste. The purpose of this activity is to increase community awareness of waste which can be a solution to the utilization of organic waste from animal waste and coconut shells. The method used in this research is the SWOT method which is correlated with the descriptive method. The most appropriate approach to make people aware of waste by means of mentoring and counseling from beginning to end, so that it is found that Kalipuro Village has implemented the utilization of organic waste by making briquettes and biogas